TEACHING PRACTICUM: INVESTIGATING EFL PRE-SERVICE TEACHERS’ SELF-EFFICACY - Fika Megawati; Yuli Astutik (English Review: Journal of English Education, 2018)
Self-efficacy is influential in determining someone's future competence. Identifying self-efficacy towards pre-service teachers provides significant information about how competent they are in applying theoretical concepts of teaching in the real school. It also becomes reflection for the institution on the quality of courses related to TEFL carried out in the implemented curriculum. Accordingly, this study aims to investigate pre-service EFL teachers' self-efficacy during the teaching practicum. This is a qualitative study involving 27 EFL teacher candidates who conducted teaching performance in some different schools. To collect the data, online Likert scale questionnaire was disseminated to the informants. The responses were interpreted through percentage and analyzed descriptively. The results indicated that generally the pre-service teachers' self-efficacy in terms of teaching skill, constructing and applying lesson plan, assessment, and classroom management, was quite high although some of them seemed to find difficulties in carrying out some classroom activities with the students. Self-efficacy analysis towards EFL learners’ practicum gives implication to any institutional parties for preparing the better quality and program of future generation teachers.Keywords: competent; teacher candidate; self-efficacy; reflection.